Access, a zone of comprehension and intrusion - Jegatheesan, Brinda (Advances in program evaluation ;, 2008)
This volume of "Advances for Program Evaluation" examines the nature and seriousness of fieldworkers' problems of failure to gain access, achieve comprehension, and avoid intrusion. To do all three, fieldworkers' need understanding and respect of the people from whom they seek data as well as be consciously and critically aware of staging field relationships knotted with tensions of estrangement, involvement, familiarity and distance. In the nine chapters of this volume, the authors speak of access to human subjects data, dealing with methods and concerns about intrusion. Attention is given to past and current practices of personalistic studies, particularly in education, and the need for improved protection of participants.